2020
DOI: 10.1002/mar.21392
|View full text |Cite
|
Sign up to set email alerts
|

Does it really hurt? Making sense of varieties of anger

Abstract: While research has shown that consumer anger causes a range of negative consequences, the conceptualization and measurement of this emotion remain inconsistent. Some studies link anger to consumer revenge motivated by a desire to hurt the company, while others associate anger with a desire to cooperate with the company. This inconsistency is caused by the fact that anger is a broad label used to refer to almost any brand failure. We argue that, rather than considering anger as a single construct, scholars shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 80 publications
0
32
0
12
Order By: Relevance
“…Emotions (Grandey et al, 2004; Ruth et al, 2002), and in particular frustration are a key element in customer satisfaction and loyalty in service encounters (Gelbrich, 2010; Guchait & Namasivayam, 2012; Van Steenburg et al, 2013). Failure is known to generate a variety of negative emotions, such as anger, regret or frustration (Antonetti et al, 2020; Gelbrich, 2010; Harrison‐Walker, 2012, 2019a; Hudson et al, 2017). Using a valence‐based approach to emotions, Smith and Bolton (2002) showed that the magnitude and type of service failure impacted negative emotions with subsequent effects on satisfaction.…”
Section: Emotions After Service Failurementioning
confidence: 99%
See 4 more Smart Citations
“…Emotions (Grandey et al, 2004; Ruth et al, 2002), and in particular frustration are a key element in customer satisfaction and loyalty in service encounters (Gelbrich, 2010; Guchait & Namasivayam, 2012; Van Steenburg et al, 2013). Failure is known to generate a variety of negative emotions, such as anger, regret or frustration (Antonetti et al, 2020; Gelbrich, 2010; Harrison‐Walker, 2012, 2019a; Hudson et al, 2017). Using a valence‐based approach to emotions, Smith and Bolton (2002) showed that the magnitude and type of service failure impacted negative emotions with subsequent effects on satisfaction.…”
Section: Emotions After Service Failurementioning
confidence: 99%
“…Smith and Ellsworth (1985) place frustration towards the “other” responsibility end of the spectrum rather than “self” responsibility, lending support to the idea that when one blames another person for the emotion‐evoking event, frustration occurs. More recent work in the customer service literature (Antonetti et al, 2020) suggests that attribution of blame to the provider leads to “supportive anger” (i.e., frustration, irritation, annoyance) but not to “vindictive anger” (fury, rage, loathing). Other scholars also propose that attributing responsibility for perceived incompetence or inadequate training of the service provider generates frustration (Harrison‐Walker, 2012; Hudson et al, 2017).…”
Section: The Appraisals Dimensions Of Frustrationmentioning
confidence: 99%
See 3 more Smart Citations